Disruption of Protein Mannosylation Affects Candida guilliermondii Cell Wall, Immune Sensing, and Virulence - Navarro-Arias, María J.; Defosse, Tatiana A.; Dementhon, Karine; Csonka, Katalin; Mellado-Mojica, Erika; Dias Valério, Aline; González-Hernández, Roberto J.; Courdavault, Vincent; Clastre, Marc; Hernández, Nahúm V.; Pérez-García, Luis A.; Singh, Dhirendra K.; et al. (Frontiers in Microbiology, 2016)
The fungal cell wall contains glycoproteins that interact with the host immune system. In the prominent pathogenic yeast Candida albicans, Pmr1 acts as a Golgi-resident ion pump that provides cofactors to mannosyltransferases, regulating the synthesis of mannans attached to glycoproteins. To gain insight into a putative conservation of such a crucial process within opportunistic yeasts, we were particularly interested in studying the role of the PMR1 homolog in a low-virulent species that rarely causes candidiasis, Candida guilliermondii. We disrupted C. guilliermondii PMR1 and found that loss of Pmr1 affected cell growth and morphology, biofilm formation, susceptibility to cell wall perturbing agents, mannan levels, and the wall composition and organization. Despite there was a significant increment in the amount of β1,3-glucan exposed at the wall surface, this positively influenced only the ability of the mutant to stimulate IL-10 production by human monocytes, suggesting that recognition of both mannan and β1,3-glucan, is required to stimulate strong levels of pro-inflammatory cytokines. Accordingly, our results indicate C. guilliermondii sensing by monocytes was critically dependent on the recognition of N-linked mannans and β1,3-glucan, as reported in other Candida species. In addition, chemical remotion of cell wall O-linked mannans was found to positively influence the recognition of C. guilliermondii by human monocytes, suggesting that O-linked mannans mask other cell wall components from immune cells. This observation contrasts with that reported in C. albicans. Finally, mice infected with C. guilliermondii pmr1 null mutant cells had significantly lower fungal burdens compared to animals challenged with the parental strain. Accordingly, the null mutant showed inability to kill larvae in the Galleria mellonella infection model. This study thus demonstrates that mannans are relevant for the C. guilliermondii-host interaction, with an atypical role for O-linked mannans.